U DTF?: A Study on The Engagement and Affective Responses of College Students in Casual Sexual Relationships - Cortes, Trisha Joy Solquia; Rei Palces, Krizna; Rungduin, Teresita (Universitas Ahmad Dahlan, 2025)
Research shows that hooking up is now part of college life, as young adulthood is where individuals explore. However, most studies tackling hookup culture are Western-centered. This research aims to study hookup culture in Manila universities, describe their possible consequences, determine perceptions, motivations, and affective responses of students who engage in hookups, and provide measures for safe sexual practices. Through narrative research, three males and three females, who were at least 18 years old, Manila college students, and experienced the culture, were interviewed. Narratives’ analysis found that students share a common understanding of what a hookup is, factors why they engage in hookup culture were determined, and they experienced emotional ambivalence following a hookup. It is recommended to provide comprehensive sexuality education, safe spaces for students to have open discussions, and competent mental health providers. Future research is needed to address the impacts of technology in spreading hookup culture.